Pengaruh Kebijakan Free Trade Zone Terhadap Penanaman Modal Asing Di Provinsi Kepulauan Riau - Muhammad Abrar; Muhammad Anshari (Jurnal Ilmu Sosial dan Ilmu Politik, 2026)
The Riau Islands Province possesses a strategic geographical location and the support of Free Trade Zone (FTZ) policies, yet the realization of Foreign Direct Investment (FDI) continues to exhibit fluctuating trends and extreme spatial inequality across regencies/cities. Departing from this phenomenon, this study aims to analyze the determinants of FDI inflows in the Riau Islands Province for the 2015–2024 period, focusing on the effectiveness of FTZ policies, road infrastructure availability, clean water supply, and the quality of Human Resources (HR). Employing an associative quantitative approach based on panel data regression across 7 regencies/cities, the model specification testing determined the Random Effect Model (REM) as the best estimator. The estimation results confirm that the FTZ area status has a positive and significant effect on accelerating FDI. Conversely, physical infrastructure variables roads and clean water and HR capacity (HDI) are proven to have no significant effect. These empirical findings emphasize that the investment attractiveness in this region is predominantly driven by fiscal and customs incentives. The anomaly regarding the insignificance of the supporting variables indicates the specific characteristics of archipelago investments where investors rely more on maritime port connectivity and independent private industrial utilities, and are dominated by efficiency-seeking FDI that prioritizes labor-intensive wage efficiency. As a policy implication, the government is recommended to maintain the stability of FTZ regulations while reorienting infrastructure development to better align with the maritime industry ecosystem.